Markets in the making : rethinking competition, goods, and innovation - Callon, Michel, 1945- (Zone Books, 2021)
"If you're convinced you know what a market is, think again. As product designers and entrepreneurs soon discover, stable commercial transactions are more enigmatic than economic theory makes them out to be. Slicing through blunt theories of supply and demand, Michel Callon presents a rigorously researched but counterintuitive model of how everyday market activity get produced, at scale"- Resumé vydavatel
Keywords: trhy; marketing; kapitalismus; spotřební zboží; zboží; markets; capitalism; consumer goods; commercial products; monografie; monographs